Abdominal Aortic Injury During Vertebroplasty. Issue 7 (1st April 2015) - Umeda, Ayako; Saeki, Noboru; Matsumoto, Chikako; Nakao, Masakazu; Kawamoto, Masashi
<x xml:space="preserve">Abstract</x> Study Design. Case report. Objective. To describe an intraoperative complication occurring from abdominal aortic penetration during a vertebroplasty procedure for vertebral fractures on Th12 and L1. Summary of Background Data. A vertebroplasty is a minimally invasive and widely performed procedure in elderly and high-risk patients, although there is a risk of life-threatening complications including aortic injury. However, little is known about the treatment of iatrogenic aortic penetration occurring during a vertebroplasty. Methods. An 80-year-old female underwent a scheduled vertebroplasty procedure. When the needle was advanced into the L1 vertebral body, arterial blood spurted out from the needle hub and fluoroscopic imaging revealed penetration of the aorta. To minimize bleeding, we depressed blood pressure and kept the needle in place. While vital signs were maintained, we prepared for blood transfusion and circulation monitoring and consulted a cardiothoracic surgeon and a cardiologist. Contrast medium injected via the needle revealed that a hematoma had formed to shift the aortic wall beyond the needle. Circulation was stable while pressure of the needle decreased, thus the hematoma was thought to have become coagulated and the needle was cautiously withdrawn. Results. After placing the patient in a supine position, aortic angiography revealed no leakage around the aorta and she was transferred to the intensive care unit. On postoperative day 1, no leakage around the aorta was confirmed on computed tomographic scans and the patient was extubated. During the 2-year follow-up period, no arterial complication was observed. Conclusion. Conservative treatment is optional for accidental aortic penetration during a vertebroplasty when a tamponade effect is expected. In cases with circulatory collapse, when the tamponade effect seems insufficient or a free wall rupture is suspected, prompt removal of the needle and surgical repair should be considered. Level of Evidence: 5